Artificial insemination of boar semen doses prepared with a low-density colloid under field conditions - Basioura, Athina; Tsakmakidis, Ioannis A.; Morrell, Jane M.; Ntallaris, Theodoros (Frontiers in Veterinary Science, 2025)
IntroductionBacterial contamination of ejaculates during semen collection is practically inevitable, and antibiotics are a constituent of semen extenders. However, bacterial resistance to antibiotics is a serious problem. The present study investigated the effect of preparing semen by centrifugation using a low-density colloid during the preparation of semen doses under field conditions, as an alternative to the use of antibiotics.MethodsFive ejaculates from four boars were each divided into two aliquots: control semen doses, which were extended with a commercial Beltsville Thawing Solution (BTS) containing antibiotics (30 × 106 spermatozoa/mL), and treated semen doses, which were processed with Porcicoll (300 × g; 20 min); the resulting sperm pellet was re-suspended in Beltsville Thawing Solution without antibiotics (30 × 106 spermatozoa/mL). Sperm motility and kinematic variables were assessed for the control and treated semen doses using computer-assisted sperm analysis (CASA). Sows were divided into two groups and inseminated with either the control or treated semen doses. In the second round, after weaning the litters from the first round, the sows in the control group were inseminated with the treated semen doses and those in the treated group received the control semen doses. For all groups, the pregnancy rate, farrowing rate, litter size, number of live-born piglets, and number of weaned piglets were recorded.ResultsNo differences (p > 0.05) between the control and treated semen doses or between the rounds were observed for any CASA-assessed motility and kinematic variables. Pregnancy (p = 0.0271) and farrowing (p = 0.046) rates were higher in the sows in the control group compared to the treated group. No differences were observed in litter size, number of live-born piglets, and number of weaned piglets (p > 0.05) between the control and treated groups, and farrowing rates were the same for the sows in both rounds. Under the current experimental conditions, sperm quality was not impaired by treatment with Porcicoll. An interesting finding is that the sows were able to become pregnant again after insemination with semen doses lacking antibiotics, with no effect on reproductive output.ConclusionIn conclusion, artificial insemination (AI) with boar semen doses processed using Porcicoll, meeting modern requirements for alternatives to antibiotics, could be a promising state-of-the-art approach.